Two-stage revision anterior cruciate ligament reconstruction using silicate-substituted calcium phosphate - Schnetzke, Marc; Vetter, Sven Y.; Linden, Philipp von der; Grützner, Paul Alfred; Recum, Jan von (Arthroscopy techniques, 2019)
Revision surgery after failed primary anterior cruciate ligament reconstruction is technically demanding. In cases in which the tunnels of the primary anterior cruciate ligament reconstruction are widened to greater than 10 mm and/or are incorrectly positioned, a 2-stage procedure enables restoration of bone stock and thus free placement of the tunnels during the revision. The gold standard for tunnel augmentation is an autologous iliac crest cancellous bone graft. However, harvesting the graft is associated with high morbidity. This article describes an alternative method for managing bone deficiencies using the synthetic bone graft substitute silicate-substituted calcium phosphate.
Gesehen am 14.04.2020